A PRELIMINARY STUDY OF THE PREVALENCE OF ANTIBODIES TO INFECTIOUS BURSAL DISEASE IN BROILER CHICKENS - A. Al-Attar , M.; K. Salman , K. (The Iraqi Journal of Veterinary Medicine, 1987)
Infectious bursal disease is one of the diseases frequently diagnosed in broilers chickens in _ Iraq depending on pathological changes in the bursa of Fabricius. It is known that maternal antibodies may interfere with the clinical signs, severity of the infection as well as the responsse of chickens to live virus vaccines. Therefore, serological surveys are of value in determining the prevalence of antibodies to this disease. The agar jel precipitation test was used in this survey because of its simplicity and specificity for detecting antigen-antibody reactions. Serum samples were collected from chickens brought to the veterinary hospital in Baghdad. Precipitation lines appeared between positive serum and antigen prepared from infected bursae and not with negative serum or negative antigen. Positive sera comprised about 67% of the total samples tested, with higher percentage of positive sera were detected among sera collected from chickens of 4-6 weeks of age